Pengembangan Lembar Kerja Peserta Didik pada Mata Pelajaran Instalasi Penerangan Listrik - Iwan Suhandri; Hastuti Hastuti (Jurnal Pendidikan Teknik Elektro, 2020)
Based on various skill competencies that exist in Vocational High Schools (SMK), there is one skill competency, namely Electrical Power Installation Engineering (TITL). One of the subjects in the TITL expertise competency is Electrical Installation which is divided into two, namely Electrical Power Installation (ITL) and Electrical Lighting Installation (IPL). Electrical Lighting Installation (IPL) is an electrical installation subject whose load is a component of lighting. For the practicum, learning requires a medium, at SMK N 1tilatang Kamang using Student Worksheets (LKPD). In this study, the aim of this research is to obtain a valid and practical LKPD in the Electrical Lighting Installation (IPL) subject. The research method used is R&D (Research & Development) and the model is 4D (Define, Design, Develop, and Disseminate). The research was conducted on class XI TITL students at SMK N 1 Tilatang Kamang. The questionnaire used in the study was to use a validation questionnaire, a teacher practicality questionnaire, and a student practicality questionnaire. On the distribution of the validation questionnaire, the average result was 0.83, with this average value, the LKPD was said to be very valid, in the distribution of the teacher practicality questionnaire and the student practicality questionnaire, the average percentage value of teacher practicality was 83%, and the percentage value the average practicality of students 89.37%. With this average value, the LKPD media is said to be very practical. Based on the results of the research data, it is stated that LKPD is very valid and practical.